2004
DOI: 10.1523/jneurosci.0123-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Efficient T-Cell Surveillance of the CNS Requires Expression of the CXC Chemokine Receptor 3

Abstract: T-cells play an important role in controlling viral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
107
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(123 citation statements)
references
References 42 publications
14
107
2
Order By: Relevance
“…These data support and extend recent studies by Thomsen and colleagues that emphasized different functional roles for chemokine receptors such as CXCR3 and CCR5 in regulating T cell accumulation within the CNS following viral infection [29,30]. Utilizing CXCR3-deficient mice, Christensen et al determined that CXCR3 is not only important for the trafficking of effector CD8 + T cells, but that it plays a role in positioning these cells in the brain during lymphocytic choriomeningitis virus (LCMV) infection [29]. Further studies by de Lemos et al investigated the roles of CXCR3 and CCR5 in CD8 + T cell trafficking to the brain using the LCMV model, and they concluded that a functional overlap between CXCR3 and CCR5 does not exist, since the absence of CCR5 did not further impair CD8 + T cell invasion of the CNS [30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data support and extend recent studies by Thomsen and colleagues that emphasized different functional roles for chemokine receptors such as CXCR3 and CCR5 in regulating T cell accumulation within the CNS following viral infection [29,30]. Utilizing CXCR3-deficient mice, Christensen et al determined that CXCR3 is not only important for the trafficking of effector CD8 + T cells, but that it plays a role in positioning these cells in the brain during lymphocytic choriomeningitis virus (LCMV) infection [29]. Further studies by de Lemos et al investigated the roles of CXCR3 and CCR5 in CD8 + T cell trafficking to the brain using the LCMV model, and they concluded that a functional overlap between CXCR3 and CCR5 does not exist, since the absence of CCR5 did not further impair CD8 + T cell invasion of the CNS [30].…”
Section: Discussionsupporting
confidence: 91%
“…Although CD8 + and CD4 + T cells expressed similar levels of CXCR3, migration of the CD8 + T cell subset was not dramatically affected, indicating differential roles for CXCR3 in trafficking of T cell subsets. These data support and extend recent studies by Thomsen and colleagues that emphasized different functional roles for chemokine receptors such as CXCR3 and CCR5 in regulating T cell accumulation within the CNS following viral infection [29,30]. Utilizing CXCR3-deficient mice, Christensen et al determined that CXCR3 is not only important for the trafficking of effector CD8 + T cells, but that it plays a role in positioning these cells in the brain during lymphocytic choriomeningitis virus (LCMV) infection [29].…”
Section: Discussionsupporting
confidence: 78%
“…NT_109320, NW_001030791, NT_039339), our analyses would indicate that CXCL10 is the relevant CXCR3 ligand expressed in the CNS during WNV encephalitis in these animals. These results agree with recent studies examining intracranial inoculation with lymphocytic choriomeningtis virus (LCMV) or dengue virus in which both CXCL10 and CXCR3 were determined to be required for the migration of virus-specific, effector T cells into LCMVinfected meninges and into dengue-infected brains (57)(58)(59). Additionally, nonredundant roles for these two chemokines were recently demonstrated in a model of HSV-1 corneal infection in which CXCL9 alone was required for CD4 T cell infiltration into this tissue site (60).…”
Section: Discussionsupporting
confidence: 90%
“…CXCL9, CXCL10, and CXCL11 lack the Glu-Leu-Arg (ELR) motif common to other members of the CXC chemokine group, and are all inducible by interferon-␥ (IFN-␥) (12,15,27,38). While these chemokines are not detectable in the healthy brain, their expression is highly upregulated following infection of the CNS with various viruses (2,3,10,21,23,24). Deficiency of CXCR3 has been associated with reduced trafficking to and/or positioning of T cells in the CNS in a number of different virally-induced disease models, such as West Nile virus encephalitis (45), mouse hepatitis virus encephalitis (43), and dengue virus encephalitis (18).…”
Section: Ymphocytic Choriomeningitis Virus (Lcmv) Is a Membermentioning
confidence: 99%